Hadith #4326 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Walid bin 'Abdullah bin Jmy' الوليد بن عبد الله بن جميع الزهري; Jabir ibn 'Abdullah; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan Abi Dawud)
I heard the crier of the Messenger of Allah (ﷺ) calling : Assemble for the prayer. I Then came out and prayed along with the Messenger of Allah (ﷺ): When the Messenger of Allah (ﷺ) finished his prayer, he sat on the pulpit laughing, and he said : Everyone should remain where he had said his prayer. He then asked : Do you know why I have assembled you? They said: Allah and His Messenger know best. He (ﷺ) said: I did not call you together fors some alarming news or for something good. Rath
Grade: Sahih